Alta disponibilidade na Plataforma TrixBox - Vargas, Tiago de Freitas (2013)
High availability is one of the most desirable properties in computer systems. This work presents a proposal to add high availability to a VoIP system based on Trixbox platform, using MySQL Cluster tool. To validate the proposal, an implementation of an experimental environment is bult composed by four virtual machines, one responsible for running the Trixbox platform, one by the node manager that orchestrates the cluster and two other running replicated storage and SQL manipulation components. From this scenario, Trixbox integration with MySQL Cluster is presented, so that all data generated in the VoIP system becomes automatically saved in the database cluster, which performs, transparently to the application, the replication of data. Experimental results show that the increase in response time generated by the replicated database is small, on the order of tens of milliseconds, and that consistency is performed properly after a fail-stop fault.